The Effects of Delay in Delivering Public Construction Projects - ALMONAYYER, KHALED ADEL (2021)
This dissertation attempts to discuss the effects and consequences of delays in delivering public construction projects of government agencies in accordance with the prevailing procurement laws and administrative contracts which differ from private contracts in terms of authority the government entity has to protect and preserve the rights of the public and the taxpayers whom are the real financiers of those projects, in addition to the contractual and legal procedures the government entity undertakes in case of delay to ensure that the rights of the public are preserved and the project agreed completion time is preserved. The dissertation also discusses the different cases and causes of delay in government projects and the extent to which the contract parties are responsible for those delays, the methods of delay analysis to determine responsibility and duration of delay, how the cost of delay is decided and calculated, conditions for applying delay damages, and enforceability of liquidated damages in case of termination. In light of the existence of several legal and judicial systems, the most important of which are the civil law and the common law, differences in the legal actions and consequences of delays in government projects in the Emirate of Dubai, which applies civil law, and the United States, which applies common law are discussed to clarify the differences in the Administrative Contracts in both countries in accordance with the enacted laws and government requirements in force. The significance of this Dissertation arises from the importance to understand the differences between administrative contracts in civil and public law jurisdictions in terms of delay damages legal definitions, legal and contractual consequences of delays, and enforceability of delay damages and their effectiveness and usefulness in achieving the governments’ intended goals in terms of completing public projects within the agreed budget and completion time, and compensating the governments for damages incurred in the event of contractor-caused delays. It is also significant that the effect of delay damages clauses on the attractiveness of government projects is considered and its effect on the pricing of these projects in light of the rights the enacted procurement laws grant the government entity to exercise in order to ensure that the interests of the public are preserved.